Exemption of Fiscal Exit Tax: Its Impact on International Flights and Tax Revenue - Joko Mariyono (Muhammadiyah University Press, 2015)
Fiscal tariff is considered as personal income tax, collected in advance when adult people who have been staying in Indonesia for more than 183 days go overseas. The magnitude of tariff was sometime much greater than the airfare itself, particularly for international flight to ASEAN member countries. This study aims to measure the impact of elimination of fiscal tariff applied to international flight passenger departing from Indonesia. Potential loss in government revenue from income tax and number of international passengers were analyzed. This study used descriptive and econometric methods. Annual and monthly time series data were collected for publication of the Indonesian Statistical Agency and Central Bank of Indonesia during the periods 2008-2012. The results show that the elimination of fiscal tariff did not affect the government revenue resulting from personal income tax. The impact of tariff elimination was to increase the rate in number of passengers going overseas.